Quality of Spine Surgery Research from the Arab Countries: A Systematic Review and Bibliometric Analysis. (21st February 2017) - Baeesa, Saleh S.; Maghrabi, Yazid; Msaddi, Abdul Karim; Assaker, Richard
Abstract : Purpose. The purpose of our study is to evaluate the level of evidence (LOE) of spine surgery publications in the Arab countries and compare it with standard international literature in spine surgery and to determine the stand of the Arab nations academic production with that of the global one. Methods. An online search using "PubMed" and "Google Scholar" was carried out, using search terms related to spine surgery such as "Spine surgery, " "Scoliosis, " "Herniated disc." Each article was reviewed and graded by two reviewers using Oxford Centre for Evidence-Based Medicine (OCEBM) Levels of Evidence scale. Results. We have identified 434 articles that met the inclusion criteria; 56% were level IV studies. The most common study design was case reports (42%). The number of Arab countries with publications in spine surgery was 18 countries. The country with the highest rate of publications was Egypt (26%). The quantity of the published studies increased from 151 in (2000–2008) to 283 in (2009–2015). There is statistical significance between high and low LOE articles (p = 0 . 0007 ). Conclusion. We have observed that LOE has not changed significantly over the period of 15 years and that much of the publications are of a low LOE (levels III and IV). We, herein, emphasize the need for spine surgeons in the Arab countries to conduct studies of higher LOE.